The Relationship Between Teacher Efficacy and Hardiness in Inclusive School Teachers at the Foundation of Inspiring Learners in Bukittinggi City - Roza Andria Lova; Zulfani Sesmiarni (International Journal of Educatio Elementaria and Psychologia, 2024)
Teachers in inclusive schools have diverse and complex responsibilities, necessitating a high level of hardiness to cope with pressure and stress. Teacher efficacy is a crucial factor that helps them face these challenges. This study aims to determine the relationship between teacher efficacy and hardiness among teachers in inclusive schools at the Yayasan Inspirasi Pembelajar in Bukittinggi. This research employs a quantitative method with a correlational approach. The analysis technique used is Pearson Product Moment. The sample consists of all teachers in inclusive schools at the Yayasan Inspirasi Pembelajar in Bukittinggi, totaling 54 individuals, obtained through total population sampling. Data collection was conducted using the Teacher Sense of Efficacy Scale and the Dispositional Resilience Scale: A Short Hardiness Scale. The results indicate a significant relationship between teacher efficacy and hardiness among inclusive school teachers. The correlation analysis shows a correlation coefficient (r) of 0.322 with a significance value (p) of 0.018 (p < 0.05). This means that the higher the level of teacher efficacy, the higher the level of hardiness they possess. These findings suggest that enhancing teacher efficacy can contribute to increasing teacher hardiness, helping them manage stress in inclusive school teaching. Therefore, it is crucial for educational institutions to provide training and support to improve teacher efficacy and thus strengthen teacher resilience.